Literasi Digital Cyber Hating dan Pelatihan Pembuatan Laporan di Yayasan Al-Farisi - Arul Budi Kalimat; Asri Nurjati Rahayu; Maya Maulidiyana; Mila Nurhayati; Ulpah Masripah; Yari Ardiansyah Rahayu (Jurnal Pengabdian Literasi Digital Indonesia, 2022)
At this time there are many school students who have carried out field assignments, namely Field Work Practicum (PKL), but many students do not understand how to make and prepare the report itself. And also the students are still unfamiliar with hate speech in social media or in real life. The RTIK Abdimas Arithmetic 3 team is currently providing ICT services at the Al-Farisi School Foundation and other general participants. With the service held at the school, one of the general services regarding Cyber ​​Hating will be carried out, followed by special services, namely guidance in making, preparing reports for the Field Work Practicum journal. It is hoped that by holding this activity the public will understand and be more biased in using social media or in real life. Before presenting the material, the team will give a pre-test to the participants to measure how far their knowledge of cyber hating is, then continue with the presentation of the material and end with a post-test in order to measure the participants in capturing the results of giving the material. And also in special services, they are expected to be able to make and compile their own reports. The solution to this problem is to make presentations from all participants by taking tests provided by the rtik abdimas team. The final result of this activity is a journal launch.